Malakhov kurgan - Zarkhy, Aleksandr; Kheifits, Iosif (Soviet Union : Tbilisskaia kinostudiia, 1944)
The film focuses on one episode in the defense of Sevastopol during World War II. It tells the story of five sailors from a sunken torpedo boat “Groznyi”, who fought at the Malakhov redoubt, one of the strongpoints of the city defense.